Litter decomposition and nutrient dynamics in a subtropical ecosystem: A comparison of natural and plantation forests (Duabanga grandiflora) in Nagaland, North-East India - Tezenle Magh; Lobeno Mozhui; L.N. Kakati; Bendang Ao; Takasangla Lemtur; Lirikum Jing (Global Ecology and Conservation)
Forest litter decomposition is vital for nutrient cycling and carbon turnover. To investigate their decomposition rate, we conducted a litter bag experiment in plantation forests (PF) and natural forests (NF) in a subtropical ecosystem. Our findings showed significant seasonal variation in litter mass loss (p < 0.0001) between the two sites, indicating seasonality as the main driver of decomposition. The decay rate constant (k) expressed in day⁻¹, reflecting the fraction of litter mass lost per day due to decomposition, reveals that NF has higher k value of 0.007 day⁻¹ than PF at 0.005 day⁻¹ , indicating faster decomposition in NF. This constant is essential for predicting litter breakdown duration, highlighting decomposition dynamics between sites, suggesting that even minimal distances between forest types can affect organic matter breakdown. In both sites, litter mass loss varied significantly from the initial to the final year (p < 0.001), with peak rates during the monsoon, followed by pre-monsoon and dry periods. Mixed litter in NF experienced a 99.94 % loss after 730 days, while PF, saw 97.80 % loss. Carbon, lignin, nitrogen, and potassium concentrations were higher during the monsoon and pre-monsoon seasons at both sites. Except for phosphorus in PF, all soil parameters positively correlated with mass loss, along with litter parameters C, N, P, K, and lignin (p < 0.001). Litter decomposition was higher in NF than PF, with significant seasonal effects (p < 0.0001), highlighting seasonality over litter mixture effects. Understanding climate variability and species diversity is essential for sustainable forest management amid ongoing anthropogenic land-use changes.